A Website Quality Model Investigating the Loyalty of South African Consumers towards Travel Websites - O. Omoruyi (Journal of Economics and Behavioral Studies, 2018)
Due to the increase in the need for travel by international visitors, it is important that organisations consider key attributes of website quality, namely information quality and system quality to encourage and enhance consumer loyalty overtime. Drawing from Delone and McLean’s theory, this research argues that information quality and system quality are antecedents of travel website quality, of which the latter is a predictor of consumer loyalty. A quantitative research approach was adopted by way of a survey methodology and data were analysed usingSmart PLS software for structural equation modelling (SEM). Based on the theoretical review, a research framework detailing the hypotheses relationships among the research constructs was developed. Based on the research findings, the results provide support for the proposed positive relationships among the research constructs.